Scenarios for Securing Content Delivery in the DRM Environment - Antonius Cahya Prihandoko; Hossein Ghodosi; Bruce Litow (Faculty of Computer Science, University of Jember, 2016)
In the DRM environment, content is usually distributed in an encrypted form. Typically,a secure encryption algorithm is utilized to accomplish such protection. However, executingthis algorithm in an insecure environment may allow adversaries to compromise the system andobtain information about the decryption key. Keeping such a key secret is a major challengefor content distribution systems. We consider two solutions for securing content delivery. Thefirst solution involves modifying the algorithm in such a way as to make implementation unintelligible.The second solution involves setting a buyer-seller protocol to communicate the keysecurely. In addition, the protocol can be set to achieve security for the content provider andprivacy protection for user. This paper describes a study of these scenarios for DRM applicationsw.r.t securing content delivery.